Edge effects in the primate community of the biological dynamics of forest fragments project, Amazonas, Brazil - Lenz, Bryan Bernard; Jack, Katharine M.; Spironello, Wilson Roberto (American Journal of Physical Anthropology, 2014)
While much is known about abiotic and vegetative edge effects in tropical forests, considerably less is known about the impact of forest edges on large mammals. In this study, we examine edge effects in a primate community to determine: 1) the distance from the edge over which edge effects in primate density are detectable, 2) whether individual species exhibit edge effects in their density, and 3) whether biological characteristics can be used to predict primate presence in edge habitats. Given their importance to many primate species, we also examine the influence of the number of large trees. We found edge penetration distances of 150 m for the five species that experienced edge effects, suggesting that primates respond to edge-related changes in the plant community that are known to be strongest over the first 150 m. Four species had higher edge densities: Alouatta macconnelli (folivore-frugivore), Chiropotes chiropotes (frugivorous seed predator), Saguinus midas (frugivore-faunivore), and Sapajus apella apella (frugivore-faunivore); one species' density was lower: Ateles paniscus (frugivore); and the final species, Pithecia chrysocephala (frugivorous seed predator), did not show an edge-related pattern. The lone significant relationship between the biological characteristics examined (body weight, diet, group size, and home range size) and primate presence in edge habitats was a negative relationship with the amount of fruit consumed. Though we did not examine primate responses to edges that border a denuded matrix, we have shown that edges influence primate distribution even following decades of secondary forest regeneration at habitat edges. © 2014 Wiley Periodicals, Inc.
Keywords: Amazona; Arboreal Species; Body Size; Body Weight; Cebus Apella; Density; Diet; Ecosystem Regeneration; Forest; Fruit; Habitat; Home Range; Nonhuman; Plant Community; Primate; Tropical Rain Forest; Animals; Forest; Anthropology, Physical; Physiology; Platyrrhini; Spatial Behavior; Animal; Anthropology, Physical; Forests; Platyrrhini; Spatial Behavior